Cross Language Sight Word Recognition of Multilingual Learners - Tejano, Leonardo (Journal of Basic Education Research, 2025)
Purpose of the study: This study explores the most frequently encountered sight words among multilingual learners in early education. It aims to compare their recognition skills across three languages—first language, national language, and English—highlighting the complexities of sight word acquisition in multilingual settings and addressing a gap in existing research. Methodology: This study employed a cross-language explanatory sequential design to examine sight word recognition among multilingual learners, specifically Ilokano speakers in the Philippines, where multilingualism is common. Most Filipinos speak at least two languages: their first language, along with Filipino (the national language) and English, which are used in formal education, government, and media. This multilingual context presents unique challenges in sight word recognition, as learners encounter sight words across these three languages. The study analyzed the frequency of sight word occurrence in educational materials and assessed recognition abilities in Ilokano, Tagalog, and English. Main Findings: The data shows that sight word recognition improves across grades, initially varying by language but converging by Grade 3. Multilingual learners' recognition rates differ based on their language background, with early proficiency in certain languages impacting initial recognition. As learners progress, proficiency in one language influences others, explaining differences in Grade 1 and Grade 2 performance. By Grade 3, recognition rates converge, reflecting research that suggests multilingual learners achieve similar proficiency levels across languages over time.